Men, machines and history : - Lilley, S. (Cobbett Press, 1948)
This book introduces about the first industrial revolution (till 3000 B.C.), the first civilizations (3000-1100 B.C.), iron, the democratic metal (1100 B.C.-A.D. 500), the second industrial revolution: embryo (500-1440), the second inductrial revolution: youth (1660-1815), the second inductrial revolution: maturity (1815-1918), materials, machine tools and production methods before 1918, between two wars (1918-39), the second World War (1939-45), retrospect and summary, appendix: the relative invention rate, suggestions for further reading, index.